(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This article examines the key methods and pedagogical principles used in teaching the foreign language. As a minority language with unique phonological, grammatical, and cultural characteristics, foreign requires an integrated instructional approach. The study highlights communicative methods, structural techniques, and technology-enhanced learning, while emphasizing fundamental principles such as learner-centered instruction, cultural relevance, and gradual progression.